2003
DOI: 10.1016/j.jacc.2003.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Incremental value of myocardial viability for prediction of Long-Term prognosis in surgically revascularized patients with left ventricular dysfunction

Abstract: Low-dose score, representing the extent of viable myocardium, has incremental prognostic value as a predictor of long-term outcome in CABG patients with LV dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Because the prognosis of patients with subendocardial infarction is better than that with transmural infarction, assessment of the transmurality of myocardial necrosis and ischemia is an important clinical issue for patients with acute myocardial infarction or with chronic myocardial ischemia (22,27). However, it has been difficult to make a diagnosis of subendocardial infarction by two-dimensional echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…Because the prognosis of patients with subendocardial infarction is better than that with transmural infarction, assessment of the transmurality of myocardial necrosis and ischemia is an important clinical issue for patients with acute myocardial infarction or with chronic myocardial ischemia (22,27). However, it has been difficult to make a diagnosis of subendocardial infarction by two-dimensional echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…4 The most important factor for successful surgical recovery may be the viability of revascularized myocardium. [11][12][13][14] Therefore, preoperative investigations should include transthoracic echocardiography to grossly evaluate ventricular function, and nuclear studies or dobutamine stress echocardiography to identify the reversibility of myocardial ischemia. In addition, coronary angiography is needed to define the affected territory.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the presence of myocardial viability was associated with a favourable outcome after revascularisation, whereas ischaemia was not predictive of prognosis. 27 In particular, WMSI during low dose dobutamine (a measure of myocardial viability) was predictive of outcome after revascularisation, whereas WMSI during high dose dobutamine (a measure of ischaemia) was not predictive. 27 …”
Section: Previous Studiesmentioning
confidence: 92%
“…Data on the relative prognostic value of viability and ischaemia in patients undergoing revascularisation are scant. [24][25][26][27] Pasquet et al 24 showed that the presence of viability (indicated by CR during low dose DSE), but not ischaemia, was a strong predictor of good outcome after revascularisation. Similarly, Sicari et al 25 26 showed that the greater the extent of viability, the lower the likelihood of cardiac death.…”
Section: Previous Studiesmentioning
confidence: 99%